Soil-derived Nature's Contributions to People and their contribution to the UN Sustainable Development Goals. (27th September 2021) - Smith, Pete; Keesstra, Saskia D.; Silver, Whendee L.; Adhya, Tapan K.; De Deyn, Gerlinde B.; Carvalheiro, Luísa G.; Giltrap, Donna L.; Renforth, Phil; Cheng, Kun; Sarkar, Binoy; Saco, Patricia M.; Scow, Kate; et al.
Abstract : This special issue provides an assessment of the contribution of soils to Nature's Contributions to People (NCP). Here, we combine this assessment and previously published relationships between NCP and delivery on the UN Sustainable Development Goals (SDGs) to infer contributions of soils to the SDGs. We show that in addition to contributing positively to the delivery of all NCP, soils also have a role in underpinning all SDGs. While highlighting the great potential of soils to contribute to sustainable development, it is recognized that poorly managed, degraded or polluted soils may contribute negatively to both NCP and SDGs. The positive contribution, however, cannot be taken for granted, and soils must be managed carefully to keep them healthy and capable of playing this vital role. A priority for soil management must include: (i) for healthy soils in natural ecosystems, protect them from conversion and degradation; (ii) for managed soils, manage in a way to protect and enhance soil biodiversity, health and sustainability and to prevent degradation; and (iii) for degraded soils, restore to full soil health. We have enough knowledge now to move forward with the implementation of best management practices to maintain and improve soil health. This analysis shows that this is not just desirable, it is essential if we are to meet the SDG targets by 2030 and achieve sustainable development more broadly in the decades to come. This article is part of the theme issue 'The role of soils in delivering Nature's Contributions to People'.